Prof. Endes Pongrác élete és munkássága visszaemlékezés születésének 110. és halálának 25 éves évfordulójára - Molnár, Péter (Gerundium, 2019)
The Life and Scientific Career of Prof. Endes Pongrác: In Memoriam of His 110Th Birthday, and the 25Th Anniversary of His Death. The study reminisces on the life and work of Prof. Pongrác Endes, through the account of the author who was a colleague and student of Endes. Professor Endes had been a dominant figure of the field of pathology at the Faculty of Medicine of the University of Debrecen for a number of years. He became a legend even before his death, and a number of anecdotes circulated about his expertise. The study is based on the presentation of the author, adjured by the Hungarian Society for the History of Medicine, and the Professor’s Club of the University of Debrecen, to celebrate the dual anniversary of Professor Endes. The presentation includes bibliographical details, in addition to interesting scientific and educational information. The tone of the study clearly indicated that the Master and student relationship between Professor Endes and the author turned into a friendship over the years.